A bioinformatics survey of the metagenome of the dinoflagellate pyrodinium bahamense var. compressum - Gonzales,David Thomas Tanco (Marine Science Institute, College of Science, University of the Philippines Diliman, 2014)
The red tide marine dinoflagellates Pyrodinium bahamense var. compressum is the main causative agent of paralytic shellfish poisoning (PSP) in the Philippines. It produces saxitoxins which are tricyclic perhydropurine alkaloid molecules that block voltage-gated neural channels. These toxins accumulate in the flesh and organs of some agriculturally important marine organisms, such as mussels and clams that feed on these dinoflagellate and cause a variety of symptoms in humans when ingested. The dinolagellate group is described with many unique characteristics, one of which is its immense and complex genome. In this study, genomic DNA and mRNA of Pyrodinium bahamense var. compressum algal cultures from Sorsogon Bay Philippines were characterize by high throughput sequencing and bioinformatics analysis. These results from a subset of the immense dinflagellate genome provide new clues for more targeted researches in harmful algal bloom (HAB) biomarkers and the saxitoxin dinoflagellate biosynthesis pathway.